Exploring the Application of the Body Image Concern Inventory Scale in Diverse Research Studies - Smita B. Thomas; Suphala Kotian, (International Journal of Management, Technology and Social Sciences (IJMTS), 2024)
Purpose:- Body Image Concern Inventory Scale (BICI), was established by Danny Axsom, Heather L. Littleton and <a href="https://www.researchgate.net/profile/Cynthia-Pury?_sg%5B0%5D=51gFt7DDlXHOMMmsitm1AsQstQpevPWP-xAWYUvjstj_zE-XLJPcCOxMiczVN20MPkk4_uQ.INBu7jR5Vsf7w7FprdPBdKlartgifljqvqE0ToWSyo3-RrUsHtzgWiLooAjCdrWdbwV112MacELVPFttmOtX6w&_sg%5B1%5D=G3iasw9YZcbgWBgbxBRU33L4iFeutch68uBfx9aFqVNBfbci_Va3slPKyvpEsAfL1YIEC9k.0n0rXbPYunQBiyXh3YPK7uD5S83hfnriYX2DBlHFmMptIJ2aMmKNh656zXuxnxCeoOw0GVdmdhJAZ_WNMyxW0Q">Cynthia L. S. Pury in 2005 to recognize the increased prevalence of body dissatisfaction and related psychological distress. The study employs assessment of the Body Image Inventory Scale used in various researches and literature articles to gather rich, in-depth insights of its reliability and validity. Methodology: The objective of this study is to delve into the intricacies of the topic at hand in 30 research articles and literatures done over 15 years. Researchers will investigate the body image perceptions and related psychological factors in various articles available online, shedding light on their potential areas of distress related to body image in female & male genders across all ages. Findings: The study provides a holistic understanding of the various researches done about body image with the help of BICI scale. The findings of this study establishes that the BICI scale proves to be a robust and dependable instrument for estimating dysmorphic apprehension in people. The scale exhibits high levels of reliability and validity, and is user friendly indicating its suitability for use in various research articles and clinical background. Originality/Value: The study reviews 30 cases using BICI scale to evaluate Body dysmorphic behaviour done in last 15 years. Paper Type: Review of prevailing literature